Access to The Utilization of Science and Technology of Sports and Familiarity of the Sports Community towards Technologically Based Devices. (April 2020) - Kristiyanto, Agus; Prasetyo, Yudik; Pratama, Kukuh Wahyudin; Karakauki, Manil; Mustapha, Aida; Idrus, Syed Zulkarnain Syed
Abstract: The advancement of sport, especially sport coaching in Indonesia, depends on the level of success of sport science and technology transfer process to sport community. This study aims (1) to describe patterns of sports science and technology transfer process to community, and (2) to analyze the level of accessibility and familiarity of the tools of technology-based physical ability test among coaches and sport community. This is a continuation of embryo research on modeling selection and utilization of technology-based devices through the Nominal Group Technique (NGT) at the research stage next year. The experiment was conducted by applying the combination method of various approaches. The approaches includes: Bibliographical Studies, Survey Descriptive, Nominal Groups Technique (NGT), as well as certain stages of a study on modeling the selection and use of hardware and software tools of modern physical ability test on sports community achievements in Surakarta. The results showed that basically the coaches have a tendency as follows: (1) 98.7% respondents felt that most coaches are ready to make improvements by training themselves in using sports science and technology, (2) 97.3% felt that a refreshing model of science and technology-based exercise planning process organized by the stakeholder group exercise can be followed periodically and coached evenly, (3) Respondents did not agree with the statement that community sports coach had appreciation for applied sports science and technology development, the lowest mean item score is the issue of "appreciation of science and technology development in sports". It is high time for coaches in Indonesia to increase their appreciation to sport science and technology, and sport community.